Financial Sector Assessment Program - Albania : Corporate Sector Financial Reporting - World Bank (World Bank, Washington, DC, 2014)
This note is prepared as part of the financial sector assessment program (FSAP). Its main objective is to describe the status and recent developments in corporate financial reporting framework in Albania and highlight key issues relevant to financial sector. The note represents a technical annex to the main FSAP aide-memoire and seeks to provide a high level overview of developments since the 2006 accounting and auditing report on the observance of standards and codes (A and A ROSC), and highlight the areas that are most relevant to the financial sector. Notable progress has been made in developing modern corporate financial reporting framework in Albania since 2006, especially in improving the statutory framework and efforts to align it with the European Union (EU) acquis communautaire. The major consequences are that there is limited financial information on corporate entities available on the market that is reliable for economic decision making or supervision of financial sector entities. The capacity and skills of institutions responsible for accounting and auditing regulation, as well as accounting and auditing profession in Albania need further development. The annex one to this note offers details on status of implementation of 2006 A and A ROSC policy recommendations.